Granulocyte-Macrophage Colony Stimulating Factor and Steroid on Neovascularization and Keratinocyte Proliferation in Wound Healing - Naim, Zainul; Supit, Laureen; Sutrisno, Eddy; Buchari, Frank Bietra (Jurnal Plastik Rekonstruksi, 2012)
Background: This study aim to evaluate the effect of subcutaneous application of recombinant human granuloctyte-macrophage colony stimulating factor (rhGM-CSF) around wounds and how it in"uences the speed of wound healing. Methods: The study utilizes Mus musculus mice in a controlled laboratory setting. Mice are divided into 3 groups: A (n = 4) receiving rhGM-CSF 10?g/kg, B (n = 4) receiving dexamethasone 10 mg/kg and C (n = 5) receiving placebo as control. Full thickness wound was made, and either rhGM-CSF, dexamethasone, or nothing were given on the wound subcutaneously for 6 days. On day 7, all rats were sacrificed and a 4-mm area from the edge of the wound were subjected for histologic examinations. Pattern of neovascularization and keratinocyte proliferation were analyzed.Results: The data shows a higher rate of neovascularization and keratinocyte proliferation in the rhGMCSF group compared to the steroid and placebo groups (p = 0.001). Not difference in the rate of keratinocyte proliferations (p = 0.085) and neovascularization (p = 0.935) are found between the dexamethasone and control groups.Discussion: Granulocyte macrophage colony stimulating factor (GM-CSF) hastens wound healing in wildtype mice by increasing the rate of keratinocyte proliferation and neovascular formation, while dexamethasone has a tendency to hinder wound healing because it acts as a GM-CSF inhibitor.